2018
DOI: 10.1029/2018tc005143
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Southern Margin of Asia During the Cretaceous: Paleomagnetic Constraints on the Lhasa‐Qiangtang Collision and the Maximum Width of the Neo‐Tethys

Abstract: The timing of the north-south collision between two terranes can be determined by the overlap of their paleolatitudes or the change of their convergence rate. For example, the overlapping paleolatitudes of the Lhasa terrane and Tethyan Himalaya and the dramatic decrease in the velocity of the Indian plate are usually ascribed to the India-Asia collision at~55 Ma. However, little is known about the paleolatitudinal evolution and velocity change of the Lhasa terrane resulting from the Lhasa-Qiangtang collision d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 111 publications
(192 reference statements)
5
36
0
Order By: Relevance
“…The crystal sizes of the magnetic minerals in this study ranged from a few to tens of micrometers. The large magnetite grains may carry a stable remanence (Ma et al, ; Yang et al, ). The rock magnetic results and EDS analysis (Figures e–h) revealed that the magnetic minerals are mainly composed of magnetite and goethite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal sizes of the magnetic minerals in this study ranged from a few to tens of micrometers. The large magnetite grains may carry a stable remanence (Ma et al, ; Yang et al, ). The rock magnetic results and EDS analysis (Figures e–h) revealed that the magnetic minerals are mainly composed of magnetite and goethite.…”
Section: Resultsmentioning
confidence: 99%
“…However, the ChRM was obtained at temperatures higher than 120 °C in this study, the unblocking temperature of goethite. Furthermore, magnetite coexisting with Fe‐oxyhydroxides may represent initial detrital iron phases (Ma et al, ). These findings imply that magnetite may have a detrital origin (Abrajevitch & Kodama, ; Ma et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 16 poles consist of 199 volcanic and 167 sedimentary rocks sites (Table S2). Noticeably, though some of the studies showed that the Cretaceous sedimentary results from the Lhasa terrane might result from significant (Tan et al, ) or a small amount (Ma et al, ) of inclination shallowing, as well as Huang et al () provide good evidence that some Eocene sedimentary rocks from the Lhasa terrane have significant inclination shallowing, considering that the 199 reliable Cretaceous volcanic sites (groups) yield an inclination‐only mean of 27.6 ± 2.0° and a corresponding paleolatitude of 14.6° ± 1.2°N, which is consistent with 26.1 ± 1.7° and 13.8 ± 1.0°N deduced from the 167 reliable Cretaceous sedimentary sites (Tables and S2), we used the paleolatitude of 14.2 ± 0.8°N calculated from the inclination‐only mean for all the 366 reliable Cretaceous paleomagnetic sites (groups) as the precollisional paleolatitude for the southern margin of Asia (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the Lhasa terrane (LT) was located at the southern margin of Asia prior to India‐Asia collision (Figure 1a), reliable Cretaceous paleomagnetic data from the LT are essential to constrain the locations and geometries of the precollisional margins of Asia. However, the published Cretaceous paleomagnetic data sets from both volcanic and sedimentary rocks yielded a wide range of inclinations range from 17.7° to 41.9°, with the consequence that the obtained paleolatitudes vary from 9.9°N to 26.7°N (Cao, Sun, Li, et al, 2017; Ma et al, 2018; Pozzi et al, 1982; Sun et al, 2008, 2012; Tan et al, 2010; Tang et al, 2013; Tong et al, 2017; Yang, Ma, Zhang, et al, 2015; Yi et al, 2015). These conspicuous inconsistencies of Cretaceous paleolatitudes of the LT provided different geometries of the Asian southern margin prior to India‐Asia collision.…”
Section: Introductionmentioning
confidence: 99%